(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): To what extent the internal marketing dimensions influence employee engagement? Purpose: This study aims at investigating the relationship between internal marketing and employee engagement in the case of the Slovenian company. Method: Using empirical data based on a survey among employees in Slovenian company this paper utilized exploratory factor analysis and regression analysis to examine the effects of internal marketing dimensions on employee engagement. Results: The results showed that two dimensions positively and significantly influence the employee engagement, namely “empathy and attention in leadership” and “work quality and awards”. Organization: The results have significant managerial implications suggesting that organizations should put the focus on internal marketing in order to enhance employee engagement. The latter is considered as an important element in achieving business excellence. Society: It is argued that internal marketing affects the important entity of society, namely employees. In addition, it could be advocated that employee engagement ultimately improve employee wellbeing. Originality: Although prior studies have found the evidence that internal marketing positively influences employee engagement, this paper further elaborates the research phenomenon through the lenses of business excellence. Limitations/Future Research: One research opportunity is to examine the factors (i.e. antecedents) that drive or hinder the internal marketing. Furthermore, the relationship between internal marketing and employee engagement could be mediated by several factors. Future studies should search for possible mediators and moderators (e.g. job satisfaction) in this relation. Increase in sample size would also improve the generalizability of the findings.